2002
DOI: 10.1590/s1413-86702002000200003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C: a critical analysis of therapeutic response predictors

Abstract: Treatment of chronic hepatitis C is still unspecific. However, there is great expectancy concerning the new pegylated interferons. As there has been much controversy about the best parameters to determine whether treatment is effective, we analyzed several criteria currently used for evaluation, including serum alanine aminotransferase (ALT) normalization, viral load reduction and improvement of hepatic histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that IFN can normalize serum alanine aminotransferase (ALT), improve liver histology and reduce viral load in patients with chronic hepatitis C (CHC). [48]…”
Section: Interferon-related Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…Several studies have shown that IFN can normalize serum alanine aminotransferase (ALT), improve liver histology and reduce viral load in patients with chronic hepatitis C (CHC). [48]…”
Section: Interferon-related Autoimmune Thyroid Diseasesmentioning
confidence: 99%